CURRENT STATUS OF KNOWLEDGE ON MANAGING SHARP EXPOSURE OF 3RD-YEAR NURSING STUDENTS AT A COLLEGE IN HANOI (Vietnam Journal of Community Medicine, 2026)
Background: Exposure to sharp objects (NSI) poses a risk of HBV, HCV, and HIV transmission and affects health and psychology. Third-year nursing students at a college in Hanoi are at high risk but lack knowledge of how to handle it. The study aims to survey third-year nursing students' current knowledge of handling sharp object exposure at a college in Hanoi.Objective: Describe the current status of knowledge of sharp object exposure handling of third-year nursing students at a college in Hanoi in 2025.Subjects and Methods: Cross-sectional descriptive study, conducted on 360 third-year nursing students from January 2025 to May 2025 at a college in Hanoi using a convenience sampling method.Results: Survey results showed that the majority of third-year nursing students at a college in Hanoi had good knowledge of handling sharps exposure (86.9%) and blood-borne pathogens (86.9%), but limited knowledge of vaccines (41.1%). Correct awareness of safe practices, such as breaking ampoules, inserting/removing IV needles, transporting and capping needles, and not picking up needles by hand, was high (from 81.1% to 96.1%), but knowledge of puncture-resistant containers, when to reuse safety containers, and handling IV needles after use was still suboptimal (49.7% - 64.4%). The rate of correct first-aid understanding after NSI was only 58.6%, while most students knew how to report incidents (97.8%) promptly. Conclusion: Research suggests a need to improve training and practice in NSI prevention and management, especially in areas where content is limited.